Oral Pancreatic Enzyme Substitution Therapy in Chronic Pancreatitis: Is Clinical Response an Appropriate Marker for Evaluation of Therapeutic Efficacy? - Domínguez-Muñoz, J Enrique; Iglesias-García, Julio (JOP. Journal of the Pancreas, 2010)
Context Malnutrition secondary to pancreatic exocrine insufficiency plays a prognostic role in chronic pancreatitis. Enzyme substitution therapy is generally prescribed to avoid diarrhea and weight loss, although it is unknown whether this is associated with normal absorption of nutrients and a normal nutritional status. Objective We aimed to evaluate whether an adequate clinical response to enzyme therapy can be used to predict a normal nutritional status in patients with chronic pancreatitis. Patients Thirty-one consecutive patients (25 males, 6 females; mean age 52 years,) with severe chronic pancreatitis and steatorrhea were enrolled in the study. Intervention Enzyme substitution therapy was indicated in cases with severe steatorrhea (more than 15 g/day), diarrhea and/or weight loss. Therapy was optimized in individual patients to obtain complete symptom relief. Main outcome measure A nutritional evaluation including body mass index and serum levels of retinol-binding protein, prealbumin and transferrin was carried out. Results Ten out of ten patients with asymptomatic steatorrhea, who did not fulfill the criteria for enzyme substitution therapy, and 11 out of 21 patients (52.4%) with symptomatic or more severe steatorrhea, who were under enzyme substitution therapy, showed a deficient nutritional status. Conclusions An appropriate clinical response to enzyme substitution therapy does not allow the prediction of a normal nutritional status in patients with chronic pancreatitis. Image: Nutritional parameters in individual patients with severe chronic pancreatitis.